The sociogenesis of modern feelings: love and friendship in Miguel de Cervantes’ “Don Quixote” and William Shakespeare’s “Romeo and Juliet” - Donskis, Leonidas (Literatūra, 2015)
William Shakespeare’s “Romeo and Juliet” reveals modern feelings – love and friendship – and their sociogenesis. Love and friendship emerge here as the feelings of a modern person. “Don Quixote of La Mancha”, the great novel by Miguel de Cervantes Saavedra, to this day keeps providing new insights and hot moral and philosophical issues for debate. “Don Quixote” is closely related to the great paradoxes of life: how to sustain our moral code in a world where morality is vanishing; how to sustain noble-mindedness and noble behaviour in a world that mocks and despises an individual precisely because he tries to sustain such behaviour. The novel depicts a dramatic crossroads of two epochs – the end of the Middle Ages and the beginning of modern times. In doing so, it offers philosophical, moral and political implications for societal existence: the loss of the moral code of chivalry and the end of medieval idealism. The psychogenesis and sociogenesis of the most intimate aspects of human exchanges – love and friendship – is approached, in the article, from the perspective of the history of consciousness.